Dry eye disease as a common ocular disorder – current knowledge and management - Rękas, Barbara; Mazurek, Wojciech; Stradczuk, Monika; Mazurek, Łukasz; Kruczyk, Barbara; Piętak, Mateusz; Gniot, Marcelina (Journal of Education, Health and Sport, 2024)
Introduction and purpose Dry eye disease is one of the most common ocular surface diseases. It is a multifactorial disease that contributes to symptoms impairing daily functioning. Dry eye syndrome occurs in up to half of the population. Therefore, proper diagnosis and treatment are necessary. The state of knowledge One of the most common causes is meibomian gland dysfunction, which leads to impaired homeostasis and easy evaporation of tears. Environmental factors such as air pollution and stimulants also influence the occurrence of dry eye syndrome. All these factors lead to bothersome symptoms such as impaired visual acuity, itching, pain or burning. Patients also complain of a feeling of sand under the eyelids or photophobia. These patients' diagnoses are based mainly on history and ophthalmologic examination. Also, the Schirmer test or fluorescein staining can be used. It is essential to quickly apply treatment, which is mainly based on Artificial tears. Artificial tears are primarily a symptomatic treatment, while they are first-line therapy. In addition, treatment can include serum drops, anti-inflammatory drugs, or supplementation with omega-3 and omega-6 acids. Summary Dry eye disease affects many people, especially the elderly. Symptoms may impair normal functioning. Untreated dry eye syndrome can also lead to many complications. Therefore, a proper diagnosis, primarily based on a basic ophthalmological examination, and individually tailored treatment are necessary. New treatment methods are described in the literature, and they seem to be promising.